Chitosan hemostatic material and preparation method thereof

By using polyurethane sponge as the skeleton in chitosan materials and using 1,4-butanediol diglycidialdehyde as the crosslinking agent, crosslinked chitosan hemostatic material with high mechanical strength and stability was prepared, solving the strength and stability of the existing materials and achieving rapid and effective hemostatic effect.

CN119746137AInactive Publication Date: 2025-04-04HUNAN YIAN BIOTECHNOLOGY CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202510001529.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing chitosan hemostasis materials have poor mechanical strength and complex preparation process, resulting in poor wet stability and cannot effectively play the role of coagulation in wounds with large amounts of bleeding.

Method used

A crosslinked chitosan hemostatic material with a polyurethane sponge as the framework material was used, and a crosslinking treatment was performed by adding 1,4-butanediol diglycidyl ether to the chitosan solution and crosslinking treatment was performed to prepare a crosslinked chitosan hemostatic material with a polyurethane sponge as the framework.

Benefits of technology

It improves the mechanical strength and wet stability of the hemostatic material, achieves rapid hemostatic and high coagulation rate, and is simple in preparation process and high in safety. It is suitable for arterial hemostatic and various wound hemostatic hemostatic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746137A_ABST
    Figure CN119746137A_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan hemostatic material in the field of biomedical technology and a preparation method thereof. The chitosan hemostatic material comprises the following steps: S1, preparing an acetic acid solution; S2, dissolving chitosan in the acetic acid solution at room temperature to obtain a chitosan solution; S3, adding 0.1% (v / v) of a cross-linking agent 1,4-butanediol diglycidyl ether to the above solution; S4, stirring evenly (5 minutes) at room temperature, and then soaking in a polyurethane (PU) sponge for 30 minutes. The chitosan hemostatic material with the polyurethane sponge as a skeleton and the preparation method thereof have reasonable structural design, and the preparation process of the chitosan hemostatic material with the polyurethane sponge as a skeleton is easy to operate, the cost is greatly reduced, the hemostasis is fast, the firmness is increased, the chitosan hemostatic material will not be damaged in clinical use, thereby increasing the safety. The chitosan hemostatic material is suitable for arterial hemostasis and various wound hemostasis, has high safety, and has great significance in clinical and daily applications such as arterial hemostasis and all wound hemostasis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedicine, in particular to a chitosan hemostatic material and a preparation method thereof. Background Art

[0002] Human bleeding can occur in various situations, such as surgery, arterial puncture (arterial interventional diagnosis and interventional treatment), combat injuries, and trauma of varying degrees in daily life. Large amounts of blood loss in the human body can lead to serious consequences and even threaten life. Uncontrolled blood loss from trauma is the second leading cause of death among civilians in daily life and the leading cause of death on the battlefield. Therefore, the research and development of hemostatic materials has always been a focus of attention at home and abroad.

[0003] To date, the hemostatic materials used clinically in the treatment of surgical bleeding are mainly degradable natural polymer derivatives, such as gelatin sponge, oxidized cellulose, microfibril collagen powder, fibrin glue and collagen sponge. However, due to their various shortcomings, they cannot meet the wide clinical needs (Hu Guoying, Gu Hanqing, New Progress in Research on the Basics and Clinical Application of Hemostatic Agents, Dialysis and Artificial Organs [J] 2010.6:21(2):29-35).

[0004] Polyurethane sponge is a polyurethane macromolecular polymer with an open cell structure. This material has special viscoelastic properties, reflects very soft material properties, and has strong impact energy absorption capacity. At present, this material is widely used in the medical field and has good biocompatibility. It is widely used in artificial hearts, kidneys, artificial skin, bandages, excipients, drug controlled release, interventional therapy catheters, etc.

[0005] Chitosan, also known as polyglucosamine (1-4)-2-amino-β-D-glucose, is a linear cationic polysaccharide obtained by partial deacetylation of chitin, which is widely present in nature. It is widely studied because it is believed to have good biocompatibility, degradability, antibacterial activity and the ability to promote wound healing. After Malette et al. published the results of the hemostatic function of chitosan in 1983, scientists began to try to use chitosan to develop hemostatic materials. In September 2002, the US FDA approved the HemCon hemostatic product produced by the US HemCon Medical Technologies. So far, the US FDA has approved the listing of chitosan hemostatic products such as HemCon hemostatic bandage, CELOX, Clo-SurP.AD, etc.

[0006] At the same time, there are also domestic and foreign patents that disclose the research results of chitosan hemostatic agents. For example, U.S. Patent US4532134 involves the optimization of chitosan material deacetylation degree, molecular weight, solvent used for dissolution, solution concentration after dissolution, and solution pH, and prepares chitosan hemostatic agents. Animal experiments have proved that chitosan hemostatic agents not only have good hemostatic effects, but also have the effects of inhibiting fibrosis and promoting tissue regeneration. Patents that directly use chitosan as a raw material to prepare hemostatic sponges include Chinese invention patent ZL0315382 0.7, 200810198164.4, 201010291789.2 and Chinese invention patent applications 02109638.4, 200680030822.8, 200110115108.5, 201110382475.8, 201210545888.8, 201210033793.8, among which Chinese invention patent 201010291789.2 discloses a novel chitosan extraction method, a chitosan hemostatic sponge is prepared by the new extraction process, and multiple chitosan hemostatic sponges are obtained after freeze-drying.

[0007] The hemostatic material is easily absorbed by the pores, and animal experiments have proved that the hemostatic material has excellent hemostatic performance. Studies have found that the mechanical strength of chitosan sponges prepared directly using chitosan as raw material is poor, so some patents for related improved methods have appeared one after another. For example, Chinese invention patent 200810198164.4 and Chinese invention patent applications 200710115108.5, 02109638.4, and 20101048730.8 disclose related technologies for preparing hemostatic sponges by mixing other natural polysaccharide materials with chitosan. However, the related preparation process is complicated and the wet stability of the obtained hemostatic agent is poor (it dissolves when it encounters blood or becomes a gel). For example, the porous hemostatic sponge prepared with chitosan and gelatin as the main components, which is the most studied at present, is easily dissolved in wounds with heavy bleeding and cannot play a coagulation role (Wu Bin, Sun Yun, etc. A method for preparing a hemostatic sponge for auxiliary materials [P]. Chinese invention patent application 201210545888.8, 2012-12-14).

[0008] In order to solve the above problems, the technology of preparing hemostatic agents by cross-linking chitosan with a cross-linking agent has been developed. For example, patent CN9110678.4 discloses the technology of adding glycerol to chitosan solution, cross-linking and curing with formaldehyde, and washing off the formaldehyde slices and encapsulating after freezing and forming. It is said that the hemostatic sponge prepared by this method is soft in texture, has good tissue compatibility with the human body, is non-toxic, and has no irritation to the wound surface; patent CN03112762.2 also provides a method for preparing sponges by cross-linking chitosan and other polysaccharides using glutaraldehyde or formaldehyde as raw materials. However, the cross-linking agents used in these patents are toxic themselves. In addition, Chinese patent applications 201110382475.8 and 201210033793.8 disclose the preparation technology of adding bioactive factors such as thrombin, antibacterial agents, plasticizers and foaming agents to chitosan hemostatic sponges. Chinese patent application 200610010064.5 disclosed the preparation and application of amphiphilic chitosan derivatives. The patent prepared N-undecyl-6-O-carboxypropyl chitosan, made into a 3% solution, added 1% glycerol and 0.5% glycerol glycidyl ether, stirred well and poured on a horizontal glass plate, and vacuum dried at 50°C to obtain a hydrogel film.

[0009] Chinese patent applications 201410727955.7 and 201410730135.3 disclose methods for preparing cross-linked chitosan hemostatic sponges, which have a long freeze-drying cycle, consume a large amount of raw materials, and consume a lot of manpower and material resources. Therefore, we propose a chitosan hemostatic material and a preparation method thereof. Summary of the invention

[0010] The purpose of the present invention is to provide a chitosan hemostatic material and a preparation method thereof to solve the problems raised in the above background technology.

[0011] To achieve the above object, the present invention provides the following technical solution: a chitosan hemostatic material and a preparation method thereof, comprising the following steps:

[0012] S1, prepare acetic acid solution;

[0013] S2, dissolving chitosan in acetic acid solution at room temperature to obtain a chitosan solution;

[0014] S3, adding 0.1% (v / v) of the cross-linking agent 1,4-butanediol diglycidyl ether to the above solution;

[0015] S4. After stirring evenly at room temperature (5 min), the mixture was placed in a polyurethane (PU) sponge and soaked for 30 min. After freeze-drying, a cross-linked chitosan hemostatic material with a polyurethane sponge as a skeleton was obtained.

[0016] Preferably, the covalent cross-linking agent is: 1,4-butanediol diglycidyl ether (BDDE), and its volume concentration in the chitosan solution is 0.1% (v / v).

[0017] Preferably, the polyurethane (PU) has a density of 30-250 kg / cm3 and a thickness of 0.3-1 cm.

[0018] Preferably, the concentration of the acetic acid solution is 0.3-3% (v / v).

[0019] Preferably, in the chitosan solution, the concentration of chitosan is 0.1-2% (w / v).

[0020] Compared with the prior art, the invention has the following beneficial effects: the chitosan hemostatic material with polyurethane sponge as the skeleton and the preparation method thereof adopt polyurethane sponge as the skeleton material and are modified with cross-linked chitosan to obtain a product with low production cost and good hemostatic effect. The invention also selects polyvinyl alcohol (PVC) sponge as the skeleton material for freeze-drying to prepare the hemostatic material, but the experimental results show that PVC is not an ideal material. The hemostatic material prepared by the invention is safe, has a high coagulation rate and fast hemostasis. The preparation process of the polyurethane chitosan hemostatic material of the invention is easy to operate, is suitable for arterial hemostasis and various wound hemostasis, has good firmness and high safety, and is of great significance in clinical and daily applications such as arterial hemostasis and all wound hemostasis. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Comparison of blood penetration and coagulation observed by blood drop observation of the sponge product of the present invention and the PU sponge product;

[0022] Figure 2 Simple1 blood penetration diagram of the present invention. DETAILED DESCRIPTION

[0023] Embodiment 1:

[0024] The present invention provides a technical solution: a chitosan hemostatic material and a preparation method thereof, comprising the following steps:

[0025] 1) preparing acetic acid solution;

[0026] 2) dissolving chitosan in acetic acid solution at room temperature;

[0027] 3) adding a cross-linking agent 1,4-butanediol diglycidyl ether to the above solution;

[0028] 4) After stirring evenly at room temperature, put in a polyurethane (PU) sponge for soaking, take out after 30 minutes, and freeze-dry to obtain a cross-linked mesh sponge hemostatic material with a polyurethane sponge as a skeleton.

[0029] In S1, the volume concentration of the acetic acid solution is 1%-3%, preferably 2%.

[0030] In S2, the mass concentration of chitosan is 1%-3%, preferably 2%.

[0031] In S3, the concentration of 1,4-butanediol diglycidyl ether is 0.01-1%, preferably 0.1% (v / v).

[0032] In S4, the density of the polyurethane sponge is 30-250kg / cm3, preferably 60-120kg / cm3.

[0033] In S4, the thickness of the polyurethane sponge is 0.3-1 cm, preferably 0.5 cm.

[0034] Embodiment 2:

[0035] The present invention provides a technical solution: a chitosan hemostatic material and a preparation method thereof, comprising the following steps:

[0036] 1) preparing acetic acid solution;

[0037] 2) dissolving chitosan in acetic acid solution at room temperature;

[0038] 3) adding a cross-linking agent 1,4-butanediol diglycidyl ether to the above solution;

[0039] 4) After stirring evenly at room temperature, put in a polyurethane (PU) sponge for soaking, take out after 30 minutes, and freeze-dry to obtain a cross-linked mesh sponge hemostatic material with a polyurethane sponge as a skeleton.

[0040] In S1, the volume concentration of the acetic acid solution is 1%-3%, preferably 2%.

[0041] In S2, the mass concentration of chitosan is 1%-3%, preferably 2%.

[0042] In S3, the concentration of 1,4-butanediol diglycidyl ether is 0.01-1%, preferably 0.1% (v / v).

[0043] In S4, the density of the polyurethane sponge is 30-250kg / cm3, preferably 60-120kg / cm3.

[0044] In S4, the thickness of the polyurethane sponge is 0.3-1 cm, preferably 0.5 cm.

[0045] Embodiment three:

[0046] The present invention provides a technical solution: a chitosan hemostatic material and a preparation method thereof, comprising the following steps:

[0047] 1) preparing acetic acid solution;

[0048] 2) dissolving chitosan in acetic acid solution at room temperature;

[0049] 3) adding a cross-linking agent 1,4-butanediol diglycidyl ether to the above solution;

[0050] 4) After stirring evenly at room temperature, put in a polyurethane (PU) sponge for soaking, take out after 30 minutes, and freeze-dry to obtain a cross-linked mesh sponge hemostatic material with a polyurethane sponge as a skeleton.

[0051] In S1, the volume concentration of the acetic acid solution is 1%-3%, preferably 2%.

[0052] In S2, the mass concentration of chitosan is 1%-3%, preferably 2%.

[0053] In S3, the concentration of 1,4-butanediol diglycidyl ether is 0.01-1%, preferably 0.1% (v / v).

[0054] In S4, the density of the polyurethane sponge is 30-250kg / cm3, preferably 60-120kg / cm3.

[0055] In S4, the thickness of the polyurethane sponge is 0.3-1 cm, preferably 0.5 cm.

[0056] Liquid absorption test

[0057] The liquid absorption of the hemostatic sponge product in the specific implementation scheme was tested with reference to the experimental method in (Fu Xiaobing, Wu Zhigu, Modern Trauma Dressing Theory and Practice [M], Beijing: Chemical Industry Press, 2007: 651). Since phosphate buffer is closer to human body fluids than water, the distilled water used in the experiment in the reference was replaced with 0.1M phosphate buffer pH 7.4 in the test.

[0058] 1) Take the hemostatic sponge products prepared in Examples 1-6 respectively, and weigh them in a dry state, which is recorded as Wdry (g);

[0059] 2) Add phosphate buffer solution at pH 7.4 to the product and soak at room temperature;

[0060] 3) After 2 hours, use a pipette and filter paper to absorb the phosphate buffer that has not been absorbed by the sponge and weigh it as Wwet (g).

[0061] 4) Calculate the liquid absorption of each product using formula 1.

[0062] Liquid absorbency = (Wwet-Wdry) / Wdry (formula 1)

[0063] Table 1. Liquid absorption of sponge products

[0064]

[0065]

[0066] + Liquid absorption: The amount of liquid absorbed by each 1g chitosan sponge product (g)

[0067] *PU sponge: Liquid absorption of three polyurethane sponges with different densities without chitosan.

[0068] It can be seen from Table 1 that the greater the density of the PU sponge, the faster the liquid absorption speed, and it reaches the wash liquid equilibrium quickly, but the liquid absorption is worse. After adding chitosan, the liquid absorption speed becomes faster, there is no difference between the densities, and the smaller the density, the better the liquid absorption.

[0069] Blood coagulation rate test

[0070] refer to

[0071] The experimental method in (Pei-Leun Kang, Shwu Jen Chang, Ioannis Manousakas, Chen Wei Lee, Chun-H su Yao, Feng-Huei Lin, Shyh Ming Kuo Development and assessment of hemostasis chitosan and stressings, Carbohydrate Polymers [J] 2011, 85: 565-570) is used to conduct a coagulation experiment on the hemostatic sponge product in the specific implementation scheme.

[0072] 1) Take the hemostatic sponge product prepared in the example and the corresponding PU sponge, cut them into 1 cm×1 cm sizes respectively, and put them into a beaker;

[0073] 2) Slowly add 0.25 ml of fresh sheep blood into the hemostatic sponge product (blood: heparin anticoagulant = 5:1);

[0074] 3) After being placed at 37°C for a preset time (1 min, 3 min), slowly pour 20 ml of purified water into the beaker along the wall of the beaker, and try not to affect the coagulation of the blood on the sponge during the pouring process;

[0075] 4) After ten minutes of placement, the red blood cells that were not absorbed by the hemostatic sponge product will be dissolved in the solution, and the absorption value is detected at a wavelength of 540nm using an ultraviolet spectrophotometer, and 0.25ml of sheep blood is dissolved in 20ml of purified water as a negative control;

[0076] 5) Use formula 2 to calculate the coagulation rate of the hemostatic sponge product.

[0077] Coagulation rate = (1-product absorbance / negative control absorbance) × 100% (Formula 2)

[0078] Table 2. Coagulation rate of sponge products

[0079]

[0080] *simple1: “Chitosan hemostatic sponge” produced by Qingdao Boyite Biomaterials Co., Ltd., patent number: ZL200610045441.9.

[0081] Take the sponge product of the present invention and the PU sponge product, drop blood and observe the blood penetration and coagulation (see the attached manual Figure 1 ), it can be seen from the figure that the chitosan sponge hemostatic material of the present invention absorbs blood and expands immediately after contacting blood, while the PU sponge does not absorb blood, but slowly absorbs blood as the density increases. Blood penetration observation was also conducted on simple1. This product absorbs blood slowly and completely absorbs blood after 15 minutes (see the attached manual). Figure 2 The hemostatic performance of the product of the present invention is greatly improved, and it can stop bleeding faster than the chitosan products on the market.

[0082] As can be seen from Table 2, the coagulation rate of the chitosan hemostatic sponge product of the present invention is above 80%, and has good coagulation performance. There is no obvious difference in the coagulation rate at 1min and 3min, indicating that the product of the present invention has a rapid coagulation effect.

[0083] Minimum breaking force test

[0084] After the hemostatic material product is obtained by freeze-drying, the hemostatic material is cut into strips with a width of 1 cm and fixed on a tensile testing machine to measure its minimum breaking force. The experiment is carried out using a dual-display dual-control tensile and compression testing machine.

[0085] The test results are shown in the table below:

[0086] Table 3. Minimum breaking force of sponge products

[0087]

Claims

1. A chitosan hemostatic material, characterized in that: The following steps are involved: S1, prepare acetic acid solution; S2, dissolving chitosan in acetic acid solution at room temperature to obtain a chitosan solution; S3, adding 0.1% (v / v) of the cross-linking agent 1,4-butanediol diglycidyl ether to the above solution; S4. After stirring evenly at room temperature (5 min), the mixture was placed in a polyurethane (PU) sponge and soaked for 30 min. After freeze-drying, a cross-linked chitosan hemostatic material with a polyurethane sponge as a skeleton was obtained.

2. The method for preparing a chitosan hemostatic material according to claim 1, characterized in that: The covalent cross-linking agent is: 1,4-butanediol diglycidyl ether (BDDE), and its volume concentration in the chitosan solution is 0.1% (v / v).

3. The method for preparing a chitosan hemostatic material according to claim 1, characterized in that: The polyurethane (PU) has a density of 30-250 kg / cm3 and a thickness of 0.3-1 cm.

4. The method for preparing a chitosan hemostatic material according to claim 1, characterized in that: The concentration of the acetic acid solution is 0.3-3% (v / v).

5. The method for preparing a chitosan hemostatic material according to claim 1, characterized in that: In the chitosan solution, the concentration of chitosan is 0.1-2% (w / v).

Citation Information

Patent Citations

  • Medical chitosan dressing and its application

    CN100443123C

  • Production and use for amphipathic chitose derivative

    CN101074271A

  • Preparation method for anti-inflammation adhesion-proof hemostatic sponge

    CN101342381A

  • Hemostasia material based on chitosan, collagen and sodium cellulose glycolate and preparation method and use thereof

    CN101450223A

  • Hemostatic compositions, assemblies, systems, and methods employing particulate hemostatic agents formed from hydrophilic polymer foam such as chitosan

    CN101594887A